Effect of Pupil Size on Optical Quality Parameters in Astigmatic Eyes Using a Double-Pass Instrument - Hidenaga Kobashi (BioMed Research International, 2013)
Purpose. To objectively determine the effects of pupil size on optical quality parameters in astigmatic eyes using a double-pass instrument. Methods. We examined twenty-two eyes of 22 healthy volunteers (mean age ± standard deviation, years) who had no ophthalmic diseases other than refractive errors (manifest cylinder ≤0.25 diopters (D)). After we fully corrected cycloplegic refraction, we created with-the-rule astigma tism of 1, 2, and 3 diopters in these eyes and then quantitatively assessed the modulation transfer function (MTF) cutoff frequency and the Strehl2D ratio with 2-, 4-, and 6-mm pupil sizes using the Optical Quality Analysis System. Results. The MTF cutoff frequency and the Strehl2D ratio decreased significantly as the amount of astigmatism increased at each pupil size ( for 2, 4, and 6 mm, analysis of variance). They also decreased significantly with an increase in pupil size at each diopter of astigmatism ( for 0, 1, 2, and 3 D). Multiple comparisons demonstrated a significant difference between measurements made for a 2-mm pupil and for a 6-mm pupil at each diopter of astigmatism ( for 0, 1, 2, and 3 D, Dunnett test) and those made for a 4-mm pupil and for a 6-mm pupil at each diopter of astigmatism ( for 0 D, 1, 2, and 3 D). Conclusions. Eyes with larger pupils had lower optical quality even when they were astigmatic. It may be necessary to correct the preexisting astigmatism to acquire excellent visual performance, especially in astigmatic eyes with larger pupils.